Chlorophyll print: an alternative approach to describe photographic printing process using nature based for photography students / Dona Lowii Madon...[et.al] - Madon, Dona Lowii; Alias, Aidah; Abdul Samat, Raziq; Zahari, Farihan; Shaari, Shafira; Sulaiman, Shaharin (2016)
Photography is not just produced in the form of prints on paper, but various preparations were made, such as creating images on stone, glass, wood, leaves and etc. With the growing fascination in unconventional canvas choices, it comes as no surprise that we're seeing leaves used in a number of interesting ways. Sensivity of printing in Chlorophyll Print were identified as new alternative solutions to do chemical free printing technique by using nature-based sources as a product to produce alternative photography printing process. This experiment dealing with varying sunlight, exposure times and different leaf specimens that can be a fulfilling and humbling way to engage the natural world as part of artworks. This can be the new education for photography students to have better understand in principles of photography and basic photographic printing technique.